Penerapan Teknologi Pembuatan Pakan Ternak Ruminansia di Desa Teluk Santong Kecamatan Plampang Kabupaten Sumbawa - Muhamad Amin; Syamsul Hidayat Dilaga; Dahlanuddin Dahlanuddin; Oscar Yanuarianto; Azhary Noersidiq (Universitas Mataram, 2026)
This community service activity was conducted to address the problem of feed scarcity faced by farmers in Teluk Santong Village, Plampang Subdistrict, Sumbawa Regency, especially during the dry season. The main issue was the limited knowledge and skills of farmers in utilizing abundant agricultural waste, such as rice straw and corn straw, as a quality feed source. The objective of this program was to enhance the farmers' capacity in feed processing through the application of ammoniation and fermentation technologies. The implementation method involved three stages: counseling through lectures, distribution of written materials (brochures), and direct hands-on demonstration with the